2011
DOI: 10.1161/circresaha.110.234146
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging Insights Into Early Inflammatory Stages of Arterial and Aortic Valve Calcification

Abstract: Traditional imaging modalities such as computed tomography, although perfectly adept at identifying and quantifying advanced calcification, cannot detect the early stages of this disorder and offer limited insight into the mechanisms of mineral dysregulation. This review presents optical molecular imaging as a promising tool that simultaneously detects pathobiological processes associated with inflammation and early stages of calcification in vivo at the (sub)cellular levels. Research into treatment of cardiov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
210
1
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(223 citation statements)
references
References 133 publications
(172 reference statements)
3
210
1
9
Order By: Relevance
“…Beyond risk of cardiovascular disease, worse CVHS has been associated with higher circulating levels of biomarkers of inflammation, endothelial dysfunction, and neurohormonal activation,18, 36, 37, 38, 39 pathways that have also been implicated in the development and progression of AV sclerosis and calcification 8, 40, 41. Lipoproteins and inflammatory cells, such as macrophages and T cells,42 have been identified in early AV lesions,43 and inflammatory activity, visualized by positron emission tomography imaging, has been documented in patients with even mild stenosis 44.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond risk of cardiovascular disease, worse CVHS has been associated with higher circulating levels of biomarkers of inflammation, endothelial dysfunction, and neurohormonal activation,18, 36, 37, 38, 39 pathways that have also been implicated in the development and progression of AV sclerosis and calcification 8, 40, 41. Lipoproteins and inflammatory cells, such as macrophages and T cells,42 have been identified in early AV lesions,43 and inflammatory activity, visualized by positron emission tomography imaging, has been documented in patients with even mild stenosis 44.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, it is well recognized that coagulation factors play a significant role in the process of inflammation and atherosclerosis 25. The attenuation of protein C has been reported to reduce anti‐apoptotic activity of the endothelial barrier and to promote local inflammation within the arterial wall,25 which is accompanied, at least to a certain degree, by calcification 26. In addition, infiltration of vascular tissue is characterized by increased oxidative stress and subsequently by endothelial dysfunction leading to increased vascular stiffness 27.…”
Section: Discussionmentioning
confidence: 99%
“…Both ex vivo and intravascular ultrasound (IVUS) studies have shown that CAC is closely related to atherosclerotic plaque burden, although the molecular basis of this process remains uncertain (15)(16)(17). Recent molecular imaging studies support the current notion that vascular calcification is not a passive degenerative process, but actually an active process that leads to ectopic mineralization promoted by the expression of multiple pro-osteogenic cytokines, transcription factors, and mineralization-regulating proteins by macrophages and other inflammatory cells (18). In this regard, fluorescence molecular multimodality imaging has shown potential to provide insightful data concerning arterial osteogenesis at much earlier stages of atherosclerosis (19,20).…”
Section: Mini-reviewmentioning
confidence: 99%
“…Regarding future alternative therapeutic approaches, the combined application of molecular imaging agents with anticalcification drugs such as bisphosphonate might potentially enable targeting at different stages of the disease (18).…”
Section: Effect Of Statins On Cacmentioning
confidence: 99%